La fausse hiérarchisation entre information nouvelle et information ancienne à l’épreuve des modèles théoriques de la politesse - Rudy Loock (Lexis: Journal in English Lexicology)
The aim of this article is to study how the ways in which new information is conveyed to a hearer can represent an act of impoliteness and how this face-theatening act or FTA (Brown & Levinson [1978, 1987]) can be softened by the use of hierarchizing structures, in particular appositive relative clauses, or by the use of softeners such as you know or as you know. We also tackle questions relating to whether the act of politeness itself must be conveyed and whether (im)politeness can be seen as a continuum. Using attested spoken examples illustrating such strategies, the ultimate aim of this article is to confront the data with the theoretical models and conceptual tools that the literature on the subject has to offer.